Współpraca Uniwersytetu Warmińsko-Mazurskiego w Olsztynie z ukraińskim Uniwersytetem Pedagogicznym w Berdiańsku – krótki epizod z historii wymiany naukowej, dydaktycznej i kulturalnej - Górniewicz, Józef (Przegląd Wschodnioeuropejski, 2023)
In the article, I analyse the effects of scientific, didactic and cultural cooperation between the University of Warmia and Mazury in Olsztyn (Poland) and the Pedagogical University in Berdiansk (Ukraine). After Poland’s accession to the European Union in 2004, Polish institutions of higher education became interesting potential partners for universities in independent Ukraine. Together with other universities in Western and Central Europe, they create a common educational space – a political, educational and cultural project. Scientific and educational aspirations, as well as great opportunities for creating the value of culture by the academic communities of Ukraine, have become the content of international cooperation of these universities. The University of Warmia and Mazury in Olsztyn has established 30 contacts with universities from Ukraine. In the article, I discuss the results of this cooperation with one of them – the Pedagogical University of Berdiansk.